Prototype of Gas Leaking Monitoring Device In Gas Distribution Pipe of PT. Prima Gasifikasi Indonesia in Tanjung Batu - Eko Prayetno; Deny Nusyirwan; Ryan Ramadhan Putra; Randika Saputra; Bayu Anggara (Jurnal Inovasi Teknologi, 2020)
This study aims to help PT. Prima Gasifikasi Indonesia makes a device that detects leaks in gas distribution pipes based on microcontroller technology. This gas detector is connected to several virtual devices that make this tool work well, namely the MQ-2 sensor working as a gas detector, NodeMCU to control the device's controls. As a notification sender to Android, the LED indicates the tool is active, and the buzzer is the provider. Information with a voice indicator. This detector can detect gas to a 'distance 'of less "than '25 cm 'from the sensor. The input on this device, namely MQ-2, will be sent directly to NodeMCU using programming, namely C language when detecting gas. From the device, two conditions will appear, the first condition is LOW when the device does not detect gas and the second condition is HIGH; namely, the device is medium detects gas caused by a leaky pipe, if the device detects gas, the 'systems will command the output in the form of a buzzer as a sound indicator to sound and provide a notification sent via the Internet to Android by giving a message that the gas has been detected